Food riots and food rights: the moral and political economy of accountability for hunger - Hossain, Naomi (UK Data Service, 2015)
There are two types of data being submitted. 1) Political Events Catalogue: The Political Events Catalogues are a compilation and coding of media reports on food-related protests in the period from 2007-2012 in the four countries of the study: India, Bangladesh, Mozambique and Kenya. There were specified criteria for the selection of media sources and for conducting searches. The data collected was categorised and coded into excel sheets. The Political Events Catalogue was compiled to get a sense of the nature and terrain of food-related protests in each country. We also compared this data to our field work to get a sense of the media bias in reporting and to understand the limitations of studies based solely on information of events gathered from the media. The quantitative analysis and graphs which were derived from the events catalogue have also been submitted. 2) Focus Group Discussion (FGD's hereafter) transcripts/notes: The second type of data which is being submitted is transcripts or notes of focus group discussions which were conducted across the four countries, in two sites each, with a wide range of actors that consisted of farmers, sellers, retailers, shopkeepers, village men and women, agricultural labourers, youth, garment workers, activists, rioters etc. In India, a total of 13 FGDs were conducted -- 6FGDs across two villages (3 in each) in Madhya Pradesh and 7FGDs across two villages in West Bengal (2 in one and 5 in the other). In Kenya, 7 FGDs were conducted in the semi-arid town of Ikutha in Kenya's Eastern province, and 7 more FGDs took place in the Mathare slums of Nairobi. The FGD transcripts from Kenya have been colour coded according to the central themes of the research. In Bangladesh, 8 FGDs where conducted in the garment industrial areas around Dhaka and 10FGDs took place in the rural Kurigram district of Northern Bangladesh. In Mozambique, 7FGDs were conducted across the two neighbourhoods of Chamanculo and Ferroviario in Maputo. The challenge of world hunger is not only about growing more food but about ensuring access to it. How can governments be made more accountable for ensuring access to food? The research addresses this question by comparing two approaches people have been taking to making governments more accountable for food security. Focusing on the ‘food crisis’ since 2007, it will examine right-to-food movements and riots over food prices in Bangladesh, India, Kenya and Mozambique. The research asks: i. How well do officials and policymakers understand how food price rises affect people? ii. How do people view government responsibilities to protect access to food? iii. Under what conditions do riots and right-to-food campaigns make governments more accountable for hunger? iv. The research will involve interviews with activists, protestors, affected groups (particularly women on low incomes), key officials and policymakers, and secondary analyses of media accounts of protests and activism, and official policy changes and statements. It will improve understanding of how to hold governments to account over hunger, enable policymakers to better anticipate and monitor the effects of food price volatility, and create opportunities for activists to engage with policymakers and government officials.